Intrauterine unilateral single inferior accessory renal artery: a case report - Singh, Punya Pratap; Kavita, Gahlot (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
In comparison with other organs, variants of blood supply to the kidneys were always at special attention due to end arteries. Anatomic variations in the renal vasculature are common and occurrence is varying in between 25% to 40%. The most common variation is presence of accessory renal arteries. Accessory renal artery generally diagnosed on abdomen angiography studies or cadaveric dissection. Only few studies or case report of intrauterine detection of accessory renal artery are available in printed and online literature. During a dedicated anomaly scan of 23 week foetus, detection of an accessory renal artery on left side entering kidney in inferior pole courses parallel to main renal arteries and arising from abdominal aorta. Knowledge of the possible anatomic variations and anomalies of the renal arteries like accessory renal arteries are necessary for proper surgical management during renal transplantation, abdominal aorta aneurysm repair, different urological procedures and angiographic procedures. As the various type of vascular and non - vascular interventions increase, knowledge of the different type of variations of the renal arteries is necessary for proper surgical management in the different specialties.